Pump-probe reflectometric and ellipsometric investigation of femtosecond laser pulse induced ablation in molybdenum - Rapp, S.; Winter, J.; Huber, H. P.; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Ultrashort pulsed laser sources offer new possibilities in precise and efficient material processing. Deep understanding of the fundamental laser-material interaction aspects is of great importance. We report on pump-probe reflectometric investigations of the ablation process on molybdenum over the complete temporal process range from the pulse impact to the final steady state. The ablation process can roughly be separated in three sections. In the first tens of picoseconds mainly the optical material properties are changed without significant material motion. Between 50 ps and a few ns the irradiated material is bulging in a spallation or phase explosion process. The actual ablation by material ejection is observed at delay times greater than 20 ns. The transient reflectivity during and in the first tens of ps after the laser irradiation in conjunction with the transient absorption influences decisively the laser-matter interaction for example when working with longer pulse durations or double pulse sequences. Direct measurements of the absorption properties by ultrafast time-resolved ellipsometry at fluences close to the ablation threshold fluence are missing to date. In this paper, pump-probe ellipsometric measurements on molybdenum - complementing the pump-probe reflectometric measurements - are presented showing ultrafast changes of the complex refractive index N = n - ik including additional information on the absorption. The imaginary part k is reduced already after 10 ps by 50% representing an increase of the optical penetration depth by a reduction of the material density. These extensive investigations pave the road towards a better understanding of pulse duration dependent laser ablation efficiency, double or burst mode laser ablation and lattice modifications in the first ps after the laser pulse impact.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Ellipsometry; Laser ablation; Reflectometry; Surface structuring; Time-resolved measurements; Transient absorption; Ultrashort pulse laser